Effects of short-term disability awareness training on attitudes of adolescent schoolboys toward persons with a disability. (September 2013) - Moore, Danielle; Nettelbeck, Ted
Abstract: Background Schoolboys ( N = 156, M age = 13 years) participated in a disability awareness training program that included guest speakers (athletes from the Paralympics and the Special Olympics), a documentary about people with a disability, a disability simulation activity, and factual information about different disabilities. Method Participants were allocated to a training program or a control condition. Subsequently, control participants completed the training program. Attitudes toward disability were measured by the Chedoke–McMaster Attitudes Towards Children With Handicaps (CATCH) Scale and the scale from the "Just Like You" disability awareness intervention, before and after training. Results Training improved attitude scores, and gains were retained at one-month follow-up. Conclusions Disability awareness training that delivered relevant information by involving guest speakers with a disability, included documentary evidence about the lives of people with a disability, and included interactive discussion, was successful. CATCH and "Just Like You" are useful tools for measuring self-reported attitudes about disability.